Anti-inflammatory effects of N-acylethanolamines in rheumatoid arthritis synovial cells are mediated by TRPV1 and TRPA1 in a COX-2 dependent manner - Lowin, Torsten (Arthritis Res Ther, 2015)
INTRODUCTION: The endocannabinoid system modulates function of immune cells and mesenchymal cells such as fibroblasts, which contribute to cartilage destruction in rheumatoid arthritis (RA). The aim of the study was to determine the influence of N-acylethanolamines anandamide (AEA), palmitoylethanolamine (PEA) and oleylethanolamine (OEA) on several features of arthritic inflammation in vitro (human material) and in vivo (a mouse model). METHODS: Immunofluorescence and western blotting were used to detect cannabinoid receptors and related enzymes. Cytokines and MMP-3 were measured by ELISA. Intracellular signaling proteins were detected by proteome profiling. Proliferation was quantified by CTB reagent. Adhesion was assessed by the xCELLigence system. After onset of collagen type II arthritis, mice were treated daily with the FAAH inhibitor JNJ1661010 (20 mg/kg) or vehicle. RESULTS: IL-6, IL-8 and MMP-3 (determined only in synovial fibroblasts (SFs)) were downregulated in primary synoviocytes and SFs of RA and OA after AEA, PEA and OEA treatment. In SFs, this was due to activation of TRPV1 and TRPA1 in a COX-2-dependent fashion. FAAH inhibition increased the efficacy of AEA in primary synoviocytes but not in SFs. The effects of OEA and PEA on SFs were diminished by FAAH inhibition. Adhesion to fibronectin was increased in a CB(1)-dependent manner by AEA in OASFs. Furthermore, elevation of endocannabinoids ameliorated collagen-induced arthritis in mice. CONCLUSIONS: N-acylethanolamines exert anti-inflammatory effects in SFs. A dual FAAH/COX-2 inhibitor, increasing N-acylethanolamine levels with concomitant TRP channel desensitization, might be a good candidate to inhibit the production of proinflammatory mediators of synovial cells and to reduce erosions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-015-0845-5) contains supplementary material, which is available to authorized users.